EFEKTIVITAS PENGGUNAAN METODE TWO STAY TWO STRAY DALAM KETERAMPILAN MEMBACA PEMAHAMAN SISWA KELAS VII SMP NEGERI 1 PALIYAN - Andi Rintoko; Siti Rochmiyati (CARAKA, 2018)
Study aims to describe (1) the reading achievement of the understanding of fable text which is learning using the lecture method (2) the learning achievement of reading the understanding of fable text which is learning using the two stay two stray model of class VII SMP Negeri 1 Paliyan. This type of research is in the form of quasi experiments (Quasi Exsperimental). The sample was taken by selected cluster random sampling class VII A with total 31 students as experimental class and class VII B total 31 students as experiment class. Data collection techniques use pretest and posttest. The validity of the question items was calculated using the correlation formula of moomen products, from 35 items obtained 22 valid matter and 13 fallen questions. Reliability calculated using Cronbach's Alpha, obtained 0.344 so that the instrument is reliable. The data analysis technique uses the t-test and the homogeneity of the variant. The results of this study show (1) learning achievement reading comprehension using lecture method in high category with average 14,645 (2) learning achievement reading comprehension using two stay two stray model in very high category with average 17,741. F-count = 64,449 (f-tabel 4,00), so it can be concluded that there is influence of learning achievement reading comprehension text of fable by using two stay two stray model in grade VII student of SMP Negeri 1 Paliyan.